2017
DOI: 10.1002/ece3.2748
|View full text |Cite
|
Sign up to set email alerts
|

A parasite's modification of host behavior reduces predation on its host

Abstract: Parasite modification of host behavior is common, and the literature is dominated by demonstrations of enhanced predation on parasitized prey resulting in transmission of parasites to their next host. We present a case in which predation on parasitized prey is reduced. Despite theoretical modeling suggesting that this phenomenon should be common, it has been reported in only a few host–parasite–predator systems. Using a system of gregarine endosymbionts in host mosquitoes, we designed experiments to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…A broad body of research demonstrates the ability of parasites to induce powerful changes in the behavior of their hosts ( Holmes & Bethel, 1972 ; Dobson, 1988 ; Moore & Gotelli, 1990 ; Lafferty & Morris, 1996 ; Moore, 2002 ; Toscano, Newsome & Griffen, 2014 ; Soghigian, Valsdottir & Livdahl, 2017 ). These changes may be adaptive for the parasite because behavioral modification often facilities transmission to the next host species in its life cycle, an adaptive response of the host species, or a non-adaptive byproduct of parasitic infection ( Lafferty, 1999 ; Levri, 1999 ; Moore, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…A broad body of research demonstrates the ability of parasites to induce powerful changes in the behavior of their hosts ( Holmes & Bethel, 1972 ; Dobson, 1988 ; Moore & Gotelli, 1990 ; Lafferty & Morris, 1996 ; Moore, 2002 ; Toscano, Newsome & Griffen, 2014 ; Soghigian, Valsdottir & Livdahl, 2017 ). These changes may be adaptive for the parasite because behavioral modification often facilities transmission to the next host species in its life cycle, an adaptive response of the host species, or a non-adaptive byproduct of parasitic infection ( Lafferty, 1999 ; Levri, 1999 ; Moore, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual reproduction occurs there through syzygy [ 24 ] and resulting oocysts remain in the host until eclosion; some parasites are released back into the larval environment upon emergence, while others are carried with adults and released during defecation or oviposition [ 29 ]. Virulence within natural hosts appears to be so low that some authors have suggested that these parasites are largely benign [ 27 , 29 , 33 ], and a recent study has shown that Ascogregarina may alter larval feeding behaviors and reduce risk of predation on their hosts [ 34 ]. However, environmental factors such as food availability and dosage of parasites can lead to elevated mortality rates and developmental delay in aquatic stages of the mosquito and reduced body size in adults [ 35 – 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…barretti were killed less often by a predator, Toxohrynchites rutilus, than compared to uninfected Ae. triseriatus [56]. This shows that while the effect of the parasite does have an effect on the competition between the two species, there are other species which might exacerbate or mitigate the effects of As.…”
Section: Discussionmentioning
confidence: 88%